Theoretical study on the interaction of polychlorotrifluoroethylene fragments with graphene-like planes - Yu. V. Hrebelna; E. M. Demianenko; M. I. Terets; A. G. Grebenyuk; Yu. I. Sementsov; N. V. Sigareva; S. M. Makhno; M. T. Kartel (Хімія, фізика та технологія поверхні)
The interaction of graphene with fragments of polychlorotrifluoroethylene (PCTFE) has been studied by quantum chemistry methods. Within the frameworks of the density functional theory with B3LYP exchange-correlation functional, 6-31G(d,p) basis set and the Grimme dispersion correction, and the second order M?ller-Plesset perturbation theory (MP2), the values of the interaction energy of graphene with polychlorotrifluoroethylene oligomers were calculated and the most probable structures of their intermolecular complexes were optimized. As a graphene model, graphene-like planes (GLP) of different sizes were chosen, namely: С40Н16, С54Н18 and С96Н24.